Sustainable Use of Greek Herbs By-Products, as an Alternative Source of Biologically Active Ingredients for Innovative Products - Dina, Evanthia; Vontzalidou, Argyro; Cheilari, Antigoni; Bagatzounis, Panagiotis; Agapidou, Eftyxia; Giannenas, Ilias; Grigoriadou, Katerina; Aligiannis, Nektarios (Frontiers in Nutrition, 2022)
The processing of medicinal and aromatic plants (MAPs) results in the production of a significant amount of plant by-products; herbal material of inferior quality and/or unusable plant parts that are not commercially exploitable. An extensive study of Greek native species was performed toward the production of innovative bioactive products using as raw materials the by-products obtained from the processing of cultivated MAPs. Origanum vulgare subsp. hirtum (oregano), Sideritis scardica (Greek mountain tea), Thymus vulgaris (thyme), and Matricaria recutita (chamomile) were selected due to their wide use for the preparation of beverages and culinary purposes. The determination of the percentage of the post-harvest processing by-products was performed for a 3 years period (2018–2020). Results showed that by-products derived from the above-mentioned species' processing constitute 64% (thyme), 54% (oregano), 37% (Greek mountain tea), and 24% (chamomile) of the total processed mass. To value the by-products as a potent source of bioactive ingredients, superior and inferior quality herbal material of the aforementioned plant species were extracted by an ultrasonic assisted extraction method. Hydroalcoholic extracts were chemically investigated using high-performance thin layer chromatography (HPTLC) and liquid chromatography-mass spectrometry (LC-MS) techniques. In addition, their free radical scavenging activity and total phenolic content (TPC) were estimated. Based on the results, herbs by-products revealed similar chemical content to the superior herbal material by the means of HPTLC and LC-MS analysis. In addition, strong free radical scavenging related to a high phenolic content was detected in the case of thyme, oregano, and Greek mountain tea. Moreover, the gas chromatography-mass spectrometry (GC-MS) analyses of the essential oils (EOs) of oregano and thyme by-products revealed the presence of carvacrol, thymol, γ-terpinene, and p-cymene among the major constituents. Finally, the LC-MS analyses of aqueous extracts of Greek mountain tea and chamomile by-products led to the identification of several bioactive compounds, such as flavonoids and phenylpropanoids. Overall, the presence of bioactive constituents in by-products, such as terpenes, phenolic compounds, and flavonoids underly their potent use as food antimicrobial and antioxidant additives, in the preparation of high added-value products, such as enriched aromatic edible oils, and innovative herbal teas, such as instant beverages.